Combination of ¹H NMR- and GC-MS-based metabonomics to study on the toxicity of Coptidis Rhizome in rats. - Yuting Zhou (Public Library of Science (PLoS), 2014)
Background Coptidis Rhizome (CR), widely applied to treat with heat and toxicity, is one of the most commonly used traditional Chinese medicine (TCM), however, an extensive dosage can induce toxicity. Diarrhea is one of the most frequent side effects of CR treatment. Methodology/principal findings In this study, metabonomics was combined with the multivariate statistical analysis to discover the endogenous metabolites which related to the diarrheal induced by CR. The male Sprague-Dawley rats were dosed with 4.95 g CR/kg weight. Urine samples were collected at day -1 (before treatment), and days 14 and 21 for NMR analysis. Serum and tissues were collected at day 14 for GC-MS analysis and histopathological examination, respectively. The urine and serum metabolic profiles provided clearer distinction between CR-treated group and control group, which was confirmed by body weight change and diarrhea. Through multivariate statistical analysis, 12 marker metabolites from ¹H NMR and 8 ones from GC-MS have been found. Among those metabolites, hippurate, acetate, alanine, glycine and glutamate are likely to break the balance of gut microbiota, whereas, lactate and 2-ketoisovalerate showed association with energy metabolism. Meanwhile, we observed that the CR-induced toxicity will recover when the treatment was stopped. Conclusions/significance These results suggest that the main reason for the CR-associated diarrhea might be disturbance in the normal gut microbiota. This metabonomics approach may provide an effective way to study the alteration of gut microbiota, which is expected to find broader application in other drug-induced gastrointestinal reaction assessment.